Diseño de una planta de tratamiento de aguas residuales municipales para el distrito de Cachicadán, Santiago de Chuco, La Libertad - 2018 - Esquivel Caipo, Denisa Aurora (2019)
This research seeks to solve the problem with respect to municipal wastewater in the district of Cachicadán by designing a municipal wastewater treatment plant, for this design the methodology of the OS standard was followed. 090 for wastewater treatment plants and the Technical Regulations for the Drinking Water and Basic Sanitation Sector, RAS 2000 and 2017, as well as the slope section method for flow rates obtaining a design flow rate of 16.39 L/s. To carry out this research, a compilation of information was made and the population was projected for the life of the WWTP in accordance with the RAS 2017, with a characterization study that determined the parameters that do not comply with the regulations in force were suspended solids with 110 mg / L, oils and fats 15.4 mg / L, DBO 344.8 mg / L, dissolved oxygen 3.94 mg / L and COD 519.93 mg / L. An aerobic process was selected for the treatment of wastewater with a yield efficiency of 95% to 98%. The location of the treatment plant has been considered in the southern zone of the district, based on data from the meteorological station of the Cachicadán district, also considering the Matrix of the Technical Regulation of the Drinking Water and Basic Sanitation Sector and surveys. The Environmental Impact Study was conducted with the Leopold matrix and baseline study, it was concluded that the appropriate process for wastewater treatment is active sludge